Operation "storm " the liberation of Negros Oriental during world war II - Cleope, Earl Jude Paul L. (2020)
The Filipino nation commemorates in 2019 the 75th anniversary of the Leyte landings during world war II in October 1944. In highlighting this historical event, it is essential to include in the narrative the local experiences of provinces and personalities during the war, particularly during 1944. In this sense, a holistic picture of the whole Visayas region is vital to provide a better view of what was going on in the Japanese occupied areas at the time of the return of American forces headed by Gen. Douglas Mac Arthur.